Exploring the Historical Development and Impact of the Ancient Roman Period - Tang, Yijian (Transactions on Social Science, Education and Humanities Research, 2024)
The historical development of the Ancient Roman period has had a profound impact on Western civilization and world culture. This study aims to explore the evolution of the political system, religious and cultural influences, artistic achievements, and literary works during the Ancient Roman period. Through the method of literature analysis, this study systematically searches and reads the relevant historical materials and academic literature in an attempt to comprehensively understand the historical development of Ancient Rome and its cultural changes. The results of this study show that the change in the political system from republican to imperial not only shaped the structure and cultural atmosphere of ancient Roman society but also provided an important example for the political system of the later generations. The religious culture of Rome underwent significant changes during the imperial period, which had a far-reaching influence on the rule and culture of the Roman Empire. Ancient Rome made outstanding achievements in the fields of art, such as architecture, sculpture, painting, and artistic style. Architectural concepts and artistic styles had a significant impact on the architecture of later generations. In literature, the works not only added luster to the culture of the time but also provided valuable resources for the literary creation of later generations. The study concludes that the historical development of the Ancient Roman period not only had a profound impact on the society at that time but also had a significant meaning on the formation and development of modern Western civilization.